Whatsapp Voice Note for Teaching Speaking to the Seventh Graders in the Pandemic Era - Dwi Ide Rahayu (Universitas Majalengka, 2021)
Some problems occur in the teaching and learning speaking to the seventh graders in the pandemic era in Indonesia. The first cause is the fact that for the seventh graders, it is their first experience in learning English formally at school since they have not learned English when they were in the elementary school. Then, the students do not have sufficient internet quota and signal. Moreover, the students also have not been digital literate yet in operating the Learning Management System. One of the solutions offered is by using the online media which is most familiarized by students, such as Whatsapp Voice Note. This study is aimed to find out (1) the students’ perception on the use of Whatsapp Voice Note in teaching and learning speaking to the seventh graders and (2) can Whasapp Voice Note improve students’ participation in the teaching and learning process. The descriptive qualitative is applied as the method of this study. The instruments are survey, interviews, and observation. The result shows that (1) the seventh graders students prefer to be taught the speaking skill by means of Whatsapp Voice Note and (2) by using Whatsapp Voice Note, most of the students are able and eager to participate more in the teaching and learning process.